Dry fungus-mediated gold bio-nanocomposite synthesis: an efficient green and sustainable heterogeneous catalyst for selective nitro reduction - Deshamukh, Amar G.; Borgohain, Rajashree; Madhyastha, Harishkumar; Patel, Paresh N. (Frontiers in Catalysis, 2025)
This dry fungus-reinforced nanoparticle synthesis is the first proficient plan of action to replace the use of hazardous chemical, physical, and other bio-methods. Here, we report the synthesis of gold bio-nanocomposites (GBNCs) via immobilization of dry biomass prepared with conventional and lyophilization methods. Under atmospheric conditions, dried Aspergillus trinidadensis VM ST01′ OL587588 functions as a reducing and capping agent in water without any solvent or buffer interference. The use of dried biomass provides additional benefits for the synthesis of GBNCs, such as short synthesis time (24 h; 36 h with wet biomass) without incubation, better shelf life (more than 18 months), improved catalytic activity, intact morphology, etc. The generated GBNCs were characterized by various analytical techniques and were found to have a roughly spherical shape with a mono-dispersed diameter of approximately 25 nm, as determined with high-resolution transmission electron microscopy. The influence of stirring and biomass concentration on the kinetics was also studied for the GBNC fabrication process. Optimized stoichiometric results have shown 3.5 × 1015 gold atoms per milligram of dried biomass prepared by both methods. The crystalline nature and surface charge of GBNCs were analyzed by powder X-ray diffraction and zeta potential studies, respectively. FT-IR studies have shown the participation of various biomass functional groups in forming GBNCs. The surface morphology of GBNCs was investigated by scanning electron microscopy. A comparative thermal stability of dried biomass and GBNCs was evaluated by thermo-gravimetric analysis, with a large difference in residual mass. Here, GBNCs have been shown to be a truly potent heterogeneous catalyst for the reduction of nitrobenzene in water using sodium borohydride with yields up to 95% isolation. The industrial suitability of GBNCs has been established with their broad operational pH (4–10) and temperature (25 °C–80 °C) ranges, reusability (more than 10 cycles), storage stability (more than 18 months), and successful scale-up investigations (up to 5 gm).